Differing disciplinary citation concentration patterns of book and journal literature?. Issue 3 (August 2016) - Chi, Pei-Shan
Highlights: Book chapters are not a suitable unit to use alongside with journal articles in bibliometric studies. Journal articles are not suitable as all types of books for the use in arts and humanities. The impact of aggregation scheme in authored books is much smaller than that in edited books. Citation window length does not influence citation concentration significantly. Abstract: A new data source providing the citation links of book publications, the Book Citation Index (BKCI), was recently released. A deeper understanding of the citation characteristics of book publications is needed before specific bibliometric indicators can be developed. In this study, the characteristics of citation distribution concentration in journal and book literature in Web of Science Core Collection (WoS), and the differences of these characteristics across fields, levels of aggregation and citation periods were probed to determine possible applications of this new data source for bibliometric studies. Even though the aggregation scheme is not sound for evaluation practices in books, aggregation matters much more for edited books in the sciences than for those in the social sciences and humanities. Journal articles have the least concentrated citation distribution in the sciences, while books play a more important role than other document types in the humanities. In the social sciences, both edited books and authored books have citation concentration distribution similar to journal articles. In addition, the Leimkuhler curves showed that citation window length (3 years vs. 9 years) does not affect the citation concentrations of most document types in journal and book literature significantly.